PENGARUH KURS RUPIAH DAN SUKU BUNGA SBI TERHADAP INDEKS HARGA SAHAM GABUNGAN ( Studi Kasus Indeks Harga Saham Gabungan pada BEI ) - Vivy - Kristinae (Universitas Tidar, 2018)
Investment growth of a country will be affected by the country's economic growth. The better the economy of a country, the better the prosperity of the population. Decrease in corporate profits will certainly affect the interest of investors to buy shares of the company concerned. In general, this will lead to a decline in the composite stock price index. The purpose of this research is to find out the influence of Exchange Rate, and SBI rate Against Composite Stock Price Index. Data were analyzed using descriptive statistics, classical assumption test and multiple linear regression. The results showed that: 0,000, sig. smaller than 0.05, then the conclusion a significant difference between exchange rate (X1), and the SBI rate (X2) simultaneously influence on the stock price index (Y). X1 = 0.103, sig. greater than 0.05, no significant difference between exchange rate (X1) simultaneously to the composite stock price index (Y). X2 = 0.000, sig. greater than 0.05, a significant difference between the SBI rate (X2) simultaneously to the composite stock price index (Y).